Pengaruh Penggunaan Social Commerce Tiktok Shop Terhadap Perilaku Konsumtif Mahasiswa/I Di Padang - Reyhan Filbert; Annisa Ulwati; Shintia Nabilla; Susriyanti . (CV. ITTC INDONESIA, 2026)
This study aims to analyze the use of social commerce platform TikTok Shop on the consumer behavior of college students in Padang. TikTok Shop has grown rapidly since 2021 and will reach 125 million users in Indonesia by 2024. This study is motivated by the high use of TikTok as a digital marketing tool, which is considered effective in increasing consumer behavior among young people. This study uses a quantitative method with a purposive sampling technique, involving 100 college students who actively shop on the TikTok Shop application. Data collection was carried out through online questionnaires to respondents who met the research criteria, and data analysis was carried out using the SPSS application. The analysis results show a significant positive influence between the use of TikTok Shop and the consumer behavior of college students in Padang. The results of this study are expected to not only enrich academic discourse related to digital marketing but also contribute to the understanding of consumer behavior in the context of digital culture.